A 1200-year history of environmental changes in Bay Jimmy area, coastal Louisiana, USA. (February 2020) - Kiage, Lawrence M
Paleoecological studies from the northern Gulf of Mexico (GOM) have mostly aimed at understanding long-term paleoenvironmental changes. Only a few studies have been performed in the southern United States focusing on paleoenvironmental changes during the common era. This study investigated paleoenvironmental changes in coastal Louisiana over the past 1200 years by utilizing proxy data, including loss-on-ignition (LOI) and pollen from a sediment core collected from a wetland in Bay Jimmy. The results indicate that the marsh in the study area was formed at ca. AD 1090 and has been primarily shaped by prevailing climatic conditions, including rare extreme events. At least four major hurricanes impacted the site over the 1200 years, including two that made landfall in recent times. The findings show that coastal Louisiana was warm and dry during the 'Medieval Warm Period' (ca. AD 950–1250). The environment after AD 1090 contained scattered Pinus and Juglans vegetation communities that were later succeeded by a closed forest that included Quercus and Morus . Red mangrove ( Rhizophora ) was established in the vicinity of Bay Jimmy until shortly after cal AD 1450 and 1640. The pollen record indicates that the 'Little Ice Age' period (AD 1550–1850) was cold and dry, characterized by a more open vegetation community. There is evidence of forest disturbance that is marked by a rise in Ambrosia pollen in the 1700s, coinciding with the time of European settlement in North America. The presence of Ambrosia and Cheno/Am pollen throughout the record suggests that anthropogenic influence has been part of the fabric of the southern Louisiana landscapes throughout the 1200 years.